Screening natural libraries of human milk oligosaccharides against lectins using CaR-ESI-MS - El-Hawiet, Amr; Chen, Yajie; Shams-Ud-Doha, Km; Kitova, Elena N.; Kitov, Pavel I.; Bode, Lars; Hage, Naim; Falcone, Franco H.; Klassen, John S. (Royal Society of Chemistry, 2017)
Human milk oligosaccharides (HMOs) afford many health benefits to breast-fed infants, such as protection against infection and regulation of the immune system, through the formation of noncovalent interactions with protein receptors. However, the molecular details of these interactions are poorly understood. Here, we describe the application of catch-and-release electrospray ionization mass spectrometry (CaR-ESI-MS) for screening natural libraries of HMOs against lectins. The HMOs in the libraries were first identified based on molecular weights (MWs), ion mobility separation arrival times (IMS-ATs) and collision-induced dissociation (CID) fingerprints of their deprotonated anions. The libraries were then screened against lectins and the ligands identified from the MWs, IMS-ATs and CID fingerprints of HMOs released from the lectin in the gas phase. To demonstrate the assay, four fractions, extracted from pooled human milk and containing ≥35 different HMOs, were screened against a C-terminal fragment of human galectin-3 (hGal-3C), for which the HMOs specificities have been previously investigated, and a fragment of the blood group antigen-binding adhesin (BabA) from Helicobacter pylori, for which the HMO specificities have not been previously established. The structures of twenty-one ligands, corresponding to both neutral and acidic HMOs, of hGal-3C were identified; all twenty one were previously shown to be ligands for this lectin. The presence of HMO ligands at six other MWs was also ascertained. Application of the assay to BabA revealed nineteen specific HMO structures that are recognized by the protein and HMO ligands at two other MWs. Notably, it was found that BabA exhibits broad specificity for HMOs, and recognizes both neutral HMOs, including non-fucosylated ones, and acidic HMOs. The results of competitive binding experiments indicate that HMOs can interact with BabA at previously unknown binding sites. The affinities of eight purified HMOs for BabA were measured by ESI-MS and found to be in the 103 M-1 to 104 M-1 range.